An 11-Year Agronomic, Economic, and Phosphorus Loss Potential Evaluation of Legacy Phosphorus Utilization in a Clay Loam Soil of the Lake Erie Basin - Zhang, Tiequan; Wang, Yutao; Tan, Chin S.; Welacky, Tom (Frontiers in Earth Science, 2020)
Legacy phosphorus (P) in agricultural soils has become a predominate source contributing to P loadings to water bodies when soil P input is balanced with crop P removal in the Canadian side of Lake Erie since mid-90’s. Use of legacy P in soils can be a ultimate and effective way to mitigate the risk of agricultural P loss and to circumvent potential P rock reserve shortage, while sustaining crop production. Questions, however, remain to be answered: whether or not halting P applications impair crop yield and farmers’ profitability, and whether or not an environmentally acceptable soil test P level can be reached in a desired time frame. A field experiment was conducted to assess the impacts of P draw-down (PDD) (i.e. use of legacy P in soils) on crop yields, P uptake and removal, and soil test P (Olsen P, an agronomic P calibration and environmental soil P risk indicator in the region) under a corn-soybean rotation in a clay loam soil of the Lake Erie basin, southwestern Ontario, Canada, from 2008 to 2018. Corn and soybean grain yields with PDD were identical to those with continuous P addition (CPA), averaged at 7.7 Mg ha-1 for corn and 3.7 Mg ha-1 for soybean, over 11 years. Similarly, no significant differences in crop P uptake and removal were found between PDD and CPA. Compared to CPA, PDD increased net farming income by CAD $104-125 ha-1yr-1 with savings on P fertilizer materials and associated application costs. Soil P loss risks with PDD reduced, as indicated by soil test P that in the top layer (0-15 cm) decreased linearly with crop production year at 3.27 mg P kg-1 yr-1 or 16.2 mg P kg-1 per 100 kg crop P removal ha-1, while in the lower soil layers, 15-90 cm, it remained unchanged. In comparison, CPA of 50 kg P ha-1 sustained soil test P in the entire soil profile, 0-90 cm, over the 11-year period. PDD can be a beneficial management practice utilizing legacy P in soils to achieve both agronomic and economic goals in an environmentally sustainable manner.